Ensuring psychological safety to develop students’ risk-based thinking of the specialty "Civil security" - Yevtushenko, N. S.; Tverdokhliebova, Natalia; Mezentseva, Iryna (Харківський національний педагогічний університет ім. Г. С. Сковороди, 2022)
Ukrainian society is exposed to external threats from the war with Russia, which negatively affects the plans, goals and quality of life, increases psychological tension and leads to a deterioration in the mental and social health of the population. This also applies to participants in the educational environment. The relevance of studying the state, experience, psychological and social capabilities of modern students is growing during the conduct of hostilities in Ukraine. Hence, the issue of psychological safety in the interaction of participants in the educational environment in distance and mixed forms of education becomes a priority. The process of forming risk-oriented thinking of students of a technical educational institution provides for training in understanding the phenomenon of risk-based thinking in the unity of three incarnations: a person himself determines what is acceptable for him, taking into account possible negative consequences, the presence of moral attitudes to preserve the life and health of people of social values of development social relations that exclude danger.

Українське суспільство зазнає зовнішніх загроз від війни з Росією, що негативно відбивається на планах, цілях і якості життя, підвищує психологічну напруженість і призводить до погіршення психічного та соціального здоров'я населення. Це стосується і учасників освітнього середовища, Актуальність вивчення стану, переживання, психологічних та соціальних можливостей сучасного студентства зростає за умов ведення воєнних дій в Україні. Звідси першочерговим стає питання психологічної безпеки у взаємодії учасників осв ітнього середовища за дистанційною та змішаною формами навчання. Педагогічний процес фо рмування ризик орієнтованого мислення студентів технічного навчального закладу передбачає навчання усвідомленню феномену ризик орієнтованого мислення в єдності трьох втілень: людина сама визначає те, що для неї прийнято з урахуванням можливих негативних на слідків, наявність моральних установок на збереження життя та здоров'я людей та соціальних цінностей розвитку суспільних відносин виключають небезпеку.
Забезпечення психологічної безпеки для формування ризико-орієнтованого мислення студентів спеціальності "Цивільна безпека"
Keywords: educational environment; educational process; psychological and pedagogical support; risk; safety; stress; освітнє середовище; освітній процес; психолого-педагогічний супровід; ризик; безпека; стрес